A study on the clusterability of latent representations in image pipelines - Wheeldon, Adrian; Serb, Alexander (Frontiers in Neuroinformatics, 2023)
Latent representations are a necessary component of cognitive artificial intelligence systems. Here, we investigate the performance of various sequential clustering algorithms on latent representations generated by autoencoder and convolutional neural network models. Results show that plain autoencoders produce latent representations which have large inter-cluster overlaps. Convolutional neural networks are shown to solve this problem, however introduce their own problems in the context of generalised cognitive pipelines. We also introduce a new algorithm, called Collage, which brings views and concepts into sequential clustering to bridge the gap with cognitive artificial intelligence. The algorithm is designed to reduce memory requirements, numbers of operations (which translate into hardware clock cycles) and thus improve energy, speed and area performance of an accelerator for running said algorithm.